Content and language integrated learning – Clil and storytelling instructions: proposta de sequência didática para processo de biletramento (português – inglês) no ensino fundamental anos iniciais do IEMA integral bilíngue - COSTA, Ingrid Barbosa da (2024)
This dissertation aims to investigate the processes of bilingualism and biliteracy from the perspective of Content and Language Integrated Learning (CLIL). It includes a review of the theoretical assumptions that underpin bilingualism and bilingual education, with the goal of creating an e-book featuring a practical didactic sequence based on the CLIL approach, emphasizing interdisciplinarity and culminating in storytelling for the implementation of an integrated curriculum in Elementary School I in public and/or private schools. The research is necessary due to the scarcity of contributions in the academic literature and the lack of experiences in public bilingual Elementary Schools at the national level. Additionally, there are challenges faced by teachers at the institution where the research was conducted regarding the integration of a curriculum that includes both components taught in English and those taught in their primary language. The theoretical foundation is based on the assumptions of Coyle, Hood, and Marsh (2010) regarding CLIL, as well as ideas from Megale (2012, 2018, 2019, 2020), García (2009), García and Wei (2014) concerning bilingualism and bilingual education, and from Soares (2020), Dias (2019, 2020) regarding literacy and biliteracy, as well as Ellis and Brewster (2014) in relation to storytelling. Methodologically, the research is classified as bibliographic and documentary in order to support the study, aiming to understand the phenomena observed during planning and implementation of the proposed activities; it includes interviews with teachers and documentation of student activities. A qualitative approach was chosen, as it provides more detailed data about the full-time routine, the adaptation period for children, the reception process, and any issues that may arise. The participants in this research are first-year Elementary School students, given their initial stage of literacy/biliteracy. As a result of the documentary consultations, classroom observations, and teacher interviews, the need for strategies that integrate content from different subjects while maintaining student engagement was identified. Thus, this work seeks to contribute to more effective bilingual educational practices, enhancing both verbal fluency and reading and writing skills in two languages in an integrated manner.